This I Believe - Fuess, Claude Moore (Tufts Archival Research Center, 2006)
Claude Fuess, Headmaster of Phillips Academy, describes himself as a "long-range optimist" who believes that the majority of today's boys are full of character and thoughtfulness, despite the newspaper headlines that suggest the moral decline of youth.